2020
DOI: 10.1186/s40545-019-0200-3
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicines: a cross-sectional study to evaluate the prevalence and predictors of use among Jordanian adults

Abstract: Introduction: Understanding why adults resort to herbal medicine can help in planning interventions aimed at increasing awareness regarding herbal use. This study sought to investigate the prevalence and to determine factors for predicting the use of herbal medicine among Jordanian adults. Methods: A cross-sectional study was conducted involving 378 older adults who were randomly selected from two different areas of Jordan. A questionnaire was used to gather data and validation criteria for validity and reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 24 publications
8
37
1
1
Order By: Relevance
“…The current study reported that the most frequently consumed herbs and natural products among the old age group were black seeds, ginger, garlic, and chilli pepper, whereas honey and murrah were more popular in the young age group. This finding is supported by a recent study in Jordan, which also reported that herbal medicine use was not associated with any demographic factors other than age ( El-Dahiyat et al, 2020 ). This might be due to the extreme difference in the daily life of the two age groups or their different flavour preferences.…”
Section: Discussionsupporting
confidence: 82%
“…The current study reported that the most frequently consumed herbs and natural products among the old age group were black seeds, ginger, garlic, and chilli pepper, whereas honey and murrah were more popular in the young age group. This finding is supported by a recent study in Jordan, which also reported that herbal medicine use was not associated with any demographic factors other than age ( El-Dahiyat et al, 2020 ). This might be due to the extreme difference in the daily life of the two age groups or their different flavour preferences.…”
Section: Discussionsupporting
confidence: 82%
“…21,31 Seventy percent of the study's participants used plants and herbs to improve their health, which is high and similar to the finding of another study conducted in Jordan to evaluate the prevalence and predictors of herbal medicine use where the prevalence was found to be 80.2%. 32 This study revealed that the majority of participants acknowledged the importance of medicinal plants and herbs in treating diseases. This shows an agreement with the findings of similar studies conducted in Morocco, 33 Tanzania, 34 the United Kingdom, 17 and Surinamese migrants in the Netherlands.…”
Section: Discussionmentioning
confidence: 89%
“…A validated questionnaire that measured pharmacists’ knowledge and attitude towards CRC early detection was developed based on literature review 24‐26 . Face and content validity were tested as described previously 27 . In more details, content validity of the questionnaire was tested qualitatively by a number of experts in clinical pharmacy and oncology research (Two PhD holders in clinical pharmacy and a clinical pharmacy master student).…”
Section: Methodsmentioning
confidence: 99%